Polemik Kebijakan Fasilitas Pajak Pertambahan Nilai Atas Air Bersih - Muh. Fahreza Haqie; Yani Sara Bauti; Vega Antaresa Rakhmat Azhari; Suparna Wijaya (Jurnalku, 2022)
This study aims to examine the impact of government policies in providing VAT facilities on the delivery of clean water. The method used in this research is qualitative with a descriptive approach. The results of the study indicate that the VAT facility that is more suitable to be provided in the provision of clean water is the VAT facility that is not collected. This facility provides benefits for the seller (clean water entrepreneur) and the buyer (citizens). With the implementation of the non-collected VAT facility policy, clean water entrepreneurs or Taxable Employers (PKP) can still credit Input Tax obtained in connection with clean water delivery activities. In addition, the burden on the citizens can also be reduced because the selling price of clean water becomes cheaper because the Input Tax that can be credited by taxable entrepreneurs don’t become an additional component in the cost of selling clean water. The government can provide a VAT Certificate of Not Being Collected (SKTD) to clean water entrepreneurs which is a requirement so that the VAT facility that is not collected can be utilized. Penelitian ini bertujuan untuk mengkaji dampak dari kebijakan pemerintah dalam memberikan fasilitas PPN terhadap penyerahan air bersih. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa fasilitas PPN yang lebih tepat diberikan atas penyerahan air bersih adalah fasilitas PPN tidak dipungut. Fasilitas ini memberikan keuntungan bagi pihak penjual (pengusaha air bersih) dan pembeli (masyarakat). Dengan diterapkannya kebijakan fasilitas PPN tidak dipungut, pengusaha air bersih atau PKP masih dapat mengkreditkan Pajak Masukan yang diperoleh sehubungan dengan kegiatan penyerahan air bersih. Selain itu, beban masyarakat juga dapat dikurangi dengan harga jual air bersih yang lebih murah, sebab Pajak Masukan yang dapat dikreditkan oleh PKP tidak menjadi komponen tambahan dalam harga pokok penjualan air bersih. Pemerintah dapat memberikan Surat Keterangan Tidak Dipungut (SKTD) PPN kepada pengusaha air bersih yang menjadi persyaratan agar fasilitas PPN tidak dipungut dapat dimanfaatkan.